Sustaining insect biodiversity in agricultural systems to ensure future food security - Jankielsohn, Astrid (Frontiers in Conservation Science, 2023)
An additional threat to sustainable food production, besides climate change, is declining biodiversity, especially in insects. To mitigate this threat, we need to determine the drivers of biodiversity decline. Insect biodiversity decline can be mainly attributed to the intensification of agriculture with the main drivers being habitat loss and use of agro-chemicals. We must view changes to more sustainable practices in agricultural management critically to determine whether these changes will sustain insect biodiversity. The first consideration for farmers is to make a profit and the priority in choosing a certain farming practice will be based on agronomic and economic gains. Damage to crops by insects, pathogens and weeds has always been a major limitation to crop yield and the management of pests, pathogens and weeds is therefore an important consideration. To reach the goal of sustaining biodiversity farmers will have to find a tradeoff between economic gain and protecting biodiversity. They will have to decide how much land they can spare for natural areas and still make a profit. Farmers will also need incentives to consider this. We will have to concentrate more on the restoration of habitats in agricultural lands and find interventions to limit the expansion of land use for agricultural development. This will enable us to reach the goal of the half-earth theory,proposed by Prof E.O. Wilson, where half of the land is conserved to safeguard biodiversity,